2011
DOI: 10.1007/s00455-011-9333-5
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Investigation of Swallowing, Nutrition, and Patient-rated Functional Impact Following Altered Fractionation Radiotherapy with Concomitant Boost for Oropharyngeal Cancer

Abstract: Altered fractionation radiotherapy for head and neck cancer has been associated with improved locoregional control, overall survival, and heightened toxicity compared with conventional treatment. Swallowing, nutrition and patient-perceived function for altered fractionation radiotherapy with concomitant boost (AFRT-CB) for T1-T3 oropharyngeal SCC has not been previously reported. Fourteen consecutive patients treated with AFRT-CB for oropharyngeal SCC were recruited from November 2006 to August 2009 in a terti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 80 publications
(67 reference statements)
1
30
0
Order By: Relevance
“…However, by 12 months post-treatment this had improved with only 7% having ongoing significant dysphagia (11). In a more recent study of the impact of AFRT with a concomitant boost (AFRT-CB) in a homogeneous group of patients with oropharyngeal cancers, the current research team found significant deterioration in functional swallowing, nutrition, and patient-rated functional impact from pretreatment to 6 weeks post-treatment, with some recovery (but still below pretreatment levels) by 6 months post-treatment (10). This pattern of improvement toward 6 months post-treatment also concurs with previous research examining quality of life (QoL) following a hyperfractionated and accelerated radiotherapy protocol (dose/fraction size <1.5-1.6Gy), which found improved outcomes at 6 and 12 months post-treatment compared to baseline (18).…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, by 12 months post-treatment this had improved with only 7% having ongoing significant dysphagia (11). In a more recent study of the impact of AFRT with a concomitant boost (AFRT-CB) in a homogeneous group of patients with oropharyngeal cancers, the current research team found significant deterioration in functional swallowing, nutrition, and patient-rated functional impact from pretreatment to 6 weeks post-treatment, with some recovery (but still below pretreatment levels) by 6 months post-treatment (10). This pattern of improvement toward 6 months post-treatment also concurs with previous research examining quality of life (QoL) following a hyperfractionated and accelerated radiotherapy protocol (dose/fraction size <1.5-1.6Gy), which found improved outcomes at 6 and 12 months post-treatment compared to baseline (18).…”
Section: Introductionmentioning
confidence: 85%
“…Acute toxicity, such as mucositis and pain, has been associated with deteriorating functional outcomes known to impact on swallowing and mastication (9), resulting in a large proportion of patients requiring modified diets and nutritional supplementation (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, in more recent literature there has been increased consideration of the functional outcomes and changes to quality of life (QoL) associated with dysphagia in the HNC population (Llewellyn, Weinman, McGurk, & Humphris, 2008;Lovell, Wong, Loh, Ngo, & Wilson, 2005;Nguyen et al, 2005). Whilst such research has furthered our understanding of the impact of dysphagia following HNC management, the majority of studies to date have applied quantitative methods to measure the extent of functional change (Barringer, Hutcheson, Sturgis, Kies, & Lewin, 2009;Cartmill, Cornwell, Ward, Davidson, & Porceddu, 2011a;Cartmill et al, 2012;Jensen et al, 2007) or change in QoL (Lovell et al, 2005;Maurer et al, 2011;Nguyen et al, 2005). The value of taking a quantitative approach has been to confirm that a problem exists (Llewellyn et al, 2008;Lovell et al, 2005;Murry, Madasu, Martin, & Robbins, 1998;Nguyen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…At 6 months post-treatment, all participants underwent a range of assessments relating to swallowing, nutrition and the functional impact of treatment which have been described in detail elsewhere [23].…”
Section: Outcome Measuresmentioning
confidence: 99%